Inhibition of Sophocarpine on Poly I: C/D-GalN-Induced Immunological Liver Injury in Mice - Huang, Yin-Qiu; Li, Peng-Yan; Wang, Jia-Bo; Zhou, Hou-Qin; Yang, Zhi-Rui; Yang, Rui-Chuang; Bai, Zhao-Fang; Wang, Li-Fu; Li, Jian-Yu; Liu, Hong-Hong; Zhao, Yan-Ling; Xiao, Xiao-He (Frontiers in Pharmacology, 2016)
Increasing evidence has suggested that natural killer (NK) cells contribute to the pathogenesis of human immunological liver injury. Previous studies have demonstrated that Sophocarpine exerts activity in immune modulation. It also has a therapeutic effect on liver protection in that it can alleviate liver fibrosis by suppressing both the activation of hepatic stellate cells and the proliferation of the activated hepatic stellate cells. However, whether Sophocarpine protects the liver by regulating NK cell activity remains unclear. In this study, the modulating effect of Sophocarpine on NK cells in the liver was investigated. The results showed that Sophocarpine dramatically decreased the production of pro-inflammatory cytokines and attenuated the liver injury induced by PolyI: C/D-GalN in C57BL/6- mice. More importantly, Sophocarpine pre-treatment significantly suppressed NK cell activation and downregulated the expression of NKG2D, a receptor responsible for NK cell activation. Moreover, the protein levels of DAP12, ZAP76 and Syk decreased, as did their corresponding mRNA levels. Overall, our study demonstrates that Sophocarpine inhibits NK cell activity, thus making it a promising therapy for immunological liver injury.